Morphological phylogeny of Reinwardtia Brauer & Bergenstamm (Diptera, Muscidae), with the description of a new species from the Neotropical region. Issue 5 (3rd July 2020) - Pérez, Sandra; Fogaça, João Manuel; Wolff, Marta; De Carvalho, Claudio José Barros
Abstract : Reinwardtia Brauer & Bergenstamm is a monotypic genus, with only R. tachinina described from Venezuela. Here, we revised the genus to include Reinwardtia bicolor sp. nov. from Colombia and Ecuador. To investigate the phylogenetic positioning of Reinwardtia, we present a morphological analysis, including 16 species of the Neotropical Reinwardtiini genera. We used 35 characters from male and female adults. Based on this phylogenetic analysis, Reinwardtia is a monophyletic genus, a sister-group of the monotypic Synthesiomyia Brauer & Bergenstamm. http://zoobank.org:pub:F8495ED0-FBDA-4A91-9A76-40B708FC6997 http://zoobank.org/urn:lsid:zoobank.org:act:8BF649B3-C9F3-4B90-B120-1CE28F051F5A